Ethnobotany in Morocco from 1990 to 2023: Part I - A critical analysis of researchers’ contributions, bibliometric, methodological attributes, and the socio-demographic characteristics of the surveyed population - Benamar, Khadija; Benelfakir, Kawtar; Benamar, Saad (Ethnobotany Research and Applications, 2026)
Background: Medicinal and aromatic plants (MAPs) have traditionally been used in Morocco’s folk medicine, reflecting the strong cultural and biodiversity background of this country. The present work aims to analyze ethnobotanical research that has been carried out about MAPs use in traditional medicine in Morocco since 1990, with a particular emphasis regarding the scope, methods and data quality. Methods: A bibliometric and methodological analysis was performed regarding ethnobotanical studies published between 1990 and 2023. Data were gathered from various scientific databases, and analyzed descriptively for publication trends, authorship, institutional contributions, study methods and surveyed populations. International collaboration was analyzed using VOSviewer (v.1.6.20), generating a full-counting country co-authorship network with modularity-based clustering. To perform the networking institutional collaborations map we used the open-source Geographical Information System software QGIS 3.38.2 Results: Ethnobotanical studies conducted in Morocco are characterized by an increase since 2018 and are predominantly undertaken by Moroccan researchers and institutions. Surveys using interviews and questionnaires (69 %) prevail over reviews. Most publications are in English (83 %) and are concentrated in high-impact journals indexed in Scopus and ScienceDirect. However, there are gaps in the reported studies, such as duration of studies, informant demographics and statistical methods. Most informants and MAPs users are women, showing their central role in traditional knowledge transmission. Conclusions: This review summarizes the growing interest in Moroccan ethnobotany, emphasizing methodological quality and reporting deficiencies. The findings encourage improved rigor and standardized data reporting to support ethnopharmacological development. Keywords: Ethnobotany; Moroccan Traditional medicine; Knowledge transmission